LEAST SQUARES DATA FITTING WITH QUADRATIC BEZIER CURVES - Suleiman, Noria A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2013)
In the present paper a numerical algorithm to construct quadratic Bezier curves for data fitting by least squares method is developed. The problem is solved by constructing so-called minimizing sequence of control points.
Keywords: data fitting; least squares method; Bezier curve